How to get promoted faster at the workplace - Khaw, Steven; Dynamic Network System (M) Sdn. Bhd. ([S.l.] : Dynamic Network System (M) Sdn. Bhd., 2003)
Contains information on faster promoting at the workplace, bonus materials and 100 management tips
Keywords: Career developement; Promotions